Colloids of naked CH 3 NH 3 PbBr 3 Perovskite Nanoparticles: Synthesis, Ssability, and thin solid film deposition - Gonzalez-Carrero, Soranyel (2018)
A novel preparation of lead halide, CH3NH3PbBr3, perovskite nanoparticle solid films from colloidal "naked" nanoparticles, that is, dispersible nanoparticles without any surfactant, is reported. The colloids are obtained by simply adding potassium ions, whose counterions are both more lipophilic and less coordinating than bromide ions, to the perovskite precursor solutions (CH3NH3Br/PbBr2 in dimethylformamide) following the reprecipitation strategy. The naked nanoparticles exhibit a low tendency to aggregate in solution, and they effectively self-assembled on a substrate by centrifugation of the colloid, leading to homogeneous nanoparticle solid films with arbitrary thickness. These results are expected to spur further the interest in lead halide perovskites due to the new opportunities offered by these films.